AN ANALYSIS CHARLIE'S PERSONALITIES IN THE PERKS OF BEING A WALLFLOWER BY USING PSYCHOANALITICAL APPROACH - Selvi Khusnul Khotimah; masulah masulah; Linda Mayasari (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2017)
This article is an analysis about human personality, especially about the correlation between adult personalitieswith childhood life. There are two research problems in this article; (1) How are Charlie’s personalities in the novel ThePerks of Being a Wallflower ?, (2) What are the correlation between Charlie’s personalities with his Childhoodlife?.Whereas, for the object of the research, this article just focused on the analysing of Charlie’s personalities that belongsto psychoanalysis aspect. This article looked deeply through Charlie’s id, ego, and superego in order to identify Charlie’spersonalities. This article also analyzed the correlation between Charlie’s personalities with his Childhood life. This articleused the novel The Perks of Being a Wallflower written by Stephen Chbosky as the object of the research and only focusedon the main character named Charlie. To support the analysis, the researcher uses psychoanalysis theories comes fromSigmund Freud. The researcher also uses the other theories that are related to the analysis which are gathered from booksand websites. This article uses qualitative research to analyze and collect data from the sources. It is because the data iscollected based on words form and the data is analyzed for description and theme using text analysis and interpreting thelarger meaning of the finding. The result of the analysis shows that Charlie’s personalities are Shy, Emotional, Honest,Caring, Uncommunicative, Hard Working, and High Sexual Desire. It also shows that Charlie’s childhood life has a big rolefor developing Charlie’s adult personalities.